1974
DOI: 10.1116/1.1318664
|View full text |Cite
|
Sign up to set email alerts
|

Step coverage in the vacuum deposition of thin metal films

Abstract: In the vacuum deposition of thin metal films the details of the film coverage over surface steps are an important consideration in many technological applications. A theory is presented which describes the relationship between the target (or emitter) and receiver (or substrate) geometry, which allows for the calculation of geometric shadowing effects between points on the receiver plane. The theory is used to formulate a computer simulation of the deposition of a film over a step on the receiver surface. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite the sources of variation discussed above for our results, a definite trend emerges from the plots in Fig. 3, Various studies involving atmospheric pressure chemical vapor deposition (APCVD) reported that the P S G film coverage exhibited a more p r o n o u n c e d reentrant profile (i.e., a decrease in O) with an increase of t/h (1,3,4,(12)(13)(14). In other A P C V D studies (5, 7), the stepcoverage angle @ was reported to increase up to 90 ~ as t/h was increased to unity, but remained at 90 ~ w h e n t/h was increased further.…”
Section: Resultsmentioning
confidence: 58%
“…Despite the sources of variation discussed above for our results, a definite trend emerges from the plots in Fig. 3, Various studies involving atmospheric pressure chemical vapor deposition (APCVD) reported that the P S G film coverage exhibited a more p r o n o u n c e d reentrant profile (i.e., a decrease in O) with an increase of t/h (1,3,4,(12)(13)(14). In other A P C V D studies (5, 7), the stepcoverage angle @ was reported to increase up to 90 ~ as t/h was increased to unity, but remained at 90 ~ w h e n t/h was increased further.…”
Section: Resultsmentioning
confidence: 58%
“…The construction method has been generalized to a larger number .of sources (68) and, in the limit, to a distributed or extended source (69,70). The latter is somewhat analogous (70) to the case where there is substrate movement, such as planetary motion (71), during deposition.…”
Section: Table II Deposition Parameters For Various Studies Of Alumin...mentioning
confidence: 99%
“…The construction method has been generalized to a larger number .of sources (68) and, in the limit, to a distributed or extended source (69,70). The latter is somewhat analogous (70) to the case where there is substrate movement, such as planetary motion (71), during deposition. It is found (69,70,72) that cracks nevertheless occur with an extended source and that (i) the bottom edge contour determines the crack depth with the depth being inversely related to the radius of curvature; (it) the top edge contour has little effect; and (~ii) at an undercut step with a reentrant angle a crack pointing toward the bottom of the undercut portion occurs.…”
Section: Table II Deposition Parameters For Various Studies Of Alumin...mentioning
confidence: 99%
“…Thus, the layer growth of these coatings can be simulated with the already existing Monte-Carlo codes, which can be found in literature [10][11][12][13][14]. In such a deposition process, the chemical reaction of the layer-forming radicals with the target or the already grown coating is more or less insignificant, because of the (low) thermal energy of the film-forming radicals.…”
Section: Comparison Of Simulation and Experimentsmentioning
confidence: 99%
“…An extension to this approach is the distinction of the various film-forming particles. By an inclusion of their sticking probability, this problem necessitates a numerical solution, which was treated in several works in the 1970's and 1980's [10][11][12][13][14]. The used simulation algorithm is the Monte-Carlo method in all cases.…”
Section: Monte-carlo Code For Analyzing Ion-solid Interactionsmentioning
confidence: 99%